Early Adolescence in Madagascar: Girls' Transitions Through Puberty in and out of School. (March 2020) - Sommer, Marni; Skolnik, Ava; Ramirez, Ana; Lee, Jana; Rasoazanany, Hariniaina; Ibitoye, Mobolaji
Evidence on girls' transitions through puberty in Madagascar and ways in which menarche influences their educational experiences and future sexual and reproductive health is limited. We conducted qualitative research involving participatory activities with girls in rural and urban Madagascar to explore their transitions through early puberty. Key informant interviews were also conducted with adults interacting in girls' lives. Findings revealed gaps in girls' knowledge and support during puberty, varying guidance received about sexuality after menarche, and challenges managing menstruation in school. Given significant gaps in girls' levels of knowledge and support, a clear need was demonstrated for educational material on puberty for early adolescents, along with teacher training about puberty. Improved toilet facilities are also needed to improve menstruating girls' school-going experiences.